The comparison of spatial resolution of ion chamber, diode, and EBT3 film based on the dose profile - Hsueh, Han-Ping; Yeh, Shyh-An; Chang, Liyun (Therapeutic Radiology and Oncology, 2019)
Background: It is essential for the physicist to quantify the dose of the radiation prior and during cancer treatment to ensure proper execution of the treatment plan. The most common way to measure the dose is utilizing Farmer chamber. The limitation of Farmer chamber is that it only provides dose of a specific point, while the beam dose profile is needed for the planning system. The Gafchromic EBT3 film can provide a quantitative dose profile in a 2D space. The EBT3 film has low energy dependence, similar effective atomic number to water, and self-developing; making it an ideal candidate for dose profile measurement. Methods: Dose profiles of EBT3 was measured, analyzed and compared to semiflex chamber and EDGE detector under same conditions. The EBT3 films were placed at the center of RW3 water phantom (30×30×30 cm3) under flattening filter free (FFF) Mode of Linac. The EBT3 films were calibrated by additional RW3 with a Farmer chamber under the stacked RW3 water phantom. Percentage depth dose (PDD) and Matlab were used to fit the dose curve of EBT3 and the results are presented. Results: The penumbra of the measured dose profile through EBT3 film demonstrated little differences when comparing with that of the EDGE detector and noticeable differences when compared to that of the semiflex chamber. For a field size of 2×2 cm2, (b=0.08, depth of 5 cm, beam off central axis 0.8 cm), the measured difference of dose profile between EBT3 and EDGE detector is –2.24%. Under the same conditions, the dose profile difference between EBT3 and semiflex chamber is 10.59%. Conclusions: This study shows that EDGE detector has the highest spatial resolution to the dose profile. EBT3 film in combination with solid phantom can quickly sample dose profile in 2D. EBT3 film can be considered to be an excellent quality assurance (QA) tool with accurate dosimetry, a good spatial resolution and tolerable dose uncertainty.